Anatomical analysis of the opposite foot to the stage of ascent and its relationship to the force produced by the high crushing hit from the center (4) in volleyball (Journal of Humanities and Social Sciences Research, 2022)
The anatomical structure of the human athlete's body, particularly the volleyball player, as well as the mechanical changes driving volleyball players' performance, including the study of the biomechanical functions of performance during the upgrading stage in the high crushing strike from the centre (4) of the opposite foot. As a result, scientific research was directed towards an accurate and insightful understanding of vital sciences, including chemistry, biomechanics, and anatomy, and a way to use these principles to improve volleyball players' skills in Iraq. Developing and correcting training methods, as well as improving the response and adaptations that occur, are fundamental to the process of mastering and benefiting from the components of science. In order to reach the required level of sports activity. The relevance of the research in setting numerical values via anatomical analysis of the stage of progress and the nature of the link between it and the generating force of the crushing talent of striking from the centre (4) in volleyball is clear from the foregoing.